Pendampingan Pembuatan Aplikasi Eduwisata Keunggulan Lokal bagi Guru PAUD di Jepara - Ratri Rahayu; Alif Catur Murti (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2020)
The problem of Early Childhood Education (ECE) teacher partners throughout the Kalinyamatan District of Jepara Regency was the non-linearity of the last education which caused the difficulties of teachers in planning learning. The knowledge and skills of ECE teachers in creating and developing android applications were also still limited. Many ECE institutions have a school recreation destination outside Jepara Regency. Therefore, ECE teachers in Kalinyamatan Subdistrict need innovative educational theme learning that is oriented to the introduction of Jepara's local excellence that is integrated with Android applications. The purpose of the holding of this mentoring activity was to improve the competence and skills of teachers in designing an Android application that contains elements of recreation as well as education by bringing the potential for local excellence in Jepara Regency. The Community Partnership Program (PKM) was carried out in ECE Kalinyamatan. PKM was held for 6 months starting from April to September 2019. The approach used in community service activities was participant active learning. The results of PKM activities are increasing the knowledge and skills of PAUD teachers in making Android-based educational applications. In addition, this PKM produces educational applications that can be used as a guide in implementing Jepara's local excellence-based recreation. Jepara's local excellence was introduced early on to PAUD students in the hope of instilling a love of products, traditions, historic sites, and culture in the surrounding environment.